2014
DOI: 10.4161/15384047.2014.972286
|View full text |Cite
|
Sign up to set email alerts
|

Gli2 silencing enhances TRAIL-induced apoptosis and reduces tumor growth in human hepatoma cells in vivo

Abstract: y These authors contributed equally to this work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 32 publications
1
6
1
Order By: Relevance
“…Our current results, for the first time, showed that depletion of GLI2 could suppress the proliferation and migration of cervical cancer cells in vitro and their tumorigenicity in vivo. These data were in line with previous observations in other cancer models, where the inhibition of GLI2 was efficient in suppressing tumorigenic properties of prostate cancer cells 17 and hepatoma cells both in vitro and in vivo 18, 19 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our current results, for the first time, showed that depletion of GLI2 could suppress the proliferation and migration of cervical cancer cells in vitro and their tumorigenicity in vivo. These data were in line with previous observations in other cancer models, where the inhibition of GLI2 was efficient in suppressing tumorigenic properties of prostate cancer cells 17 and hepatoma cells both in vitro and in vivo 18, 19 .…”
Section: Discussionsupporting
confidence: 92%
“…Clearly, our current results were consistent with all of these findings that knockdown GLI2 resulted in cell-cycle arrest at G0/G1, with reduction of cyclin D1 expression and upregulation of p21 and p27 levels, whereas overexpression of GLI2 increased proliferation. Intriguingly, while previous studies reported that GLI2 gene silencing sensitized human hepatoma cells 18, 19 and basal cell carcinoma 23 to tumor necrosis factor-related apoptosis by downregulating c-FLIP and Bcl-2, our result showed that GLI2 knockdown showed no effect on apoptosis using two apoptosis assays, including ELISA assay and Annexin-V FITC Staining. Future studies are needed to determine whether GLI2 are necessary for preventing apoptosis of cervical cancer cells when exposing to apoptosis-inducing agents.…”
Section: Discussioncontrasting
confidence: 55%
“…TRAIL could promote apoptosis in various cancer cells but not in normal cells. 3 However, TRAIL resistance occurs in many carcinomas, including endometrial carcinoma. TRAIL resistance is proposed to be due to the action of decoy receptors such as mutation in DR4 (TRAIL-RI) or DR5 (TRAIL-RII), and the dysfunction of DISC components, such as FADD, caspase-8 or 10, and c-FLIP.…”
Section: Introductionmentioning
confidence: 99%
“…In different animal models of hepatocellular carcinoma, the Hh pathway is activated in pre-cancerous tissues and cancerous tumors (Cai et al, 2016). In precursor cancerous cells, Shh promotes proliferation through induction of cyclin B1 and CDK1 mitotic proteins (Cai et al, 2016), while preventing apoptosis (Zhang et al, 2014; Wang et al, 2013). Hh also induces an epithelial to mesenchymal transition in malignant cells, favoring migration and invasiveness (Chen et al, 2014; Byrne et al, 2015).…”
Section: Hedgehog Pathway In Nonalcoholic Fatty Liver Diseasementioning
confidence: 99%